Implementation of the Exponential Comparison Method (MPE) in a Decision Support System for Selecting the Chairperson of PORSENI 2.0 at the BEM of STMIK Mardira Indonesia - Rangga Putra Aritonang; Ade Taopik Hidayatuloh; Egi Badar Sambani (Journal of Multimedia Technology and Applied Software, 2026)
The selection of the chief executive for Porseni 2.0 at BEM STMIK Mardira Indonesia plays a crucial role in ensuring the smooth execution and overall quality of the event. The current decision-making process relies heavily on subjective judgment, which may result in biased or inconsistent outcomes. To address this issue, an objective evaluation framework is required to assess candidates based on predetermined criteria. The Exponential Comparison Method (MPE) is utilized in this study due to its ability to highlight score disparities through exponential weighting. This research aims to identify relevant assessment criteria, apply the MPE method in evaluating candidates, and determine the most suitable individual based on the final ranking. The findings are expected to support the student executive board in making decisions that are transparent, measurable, and more accountable.